Economic report of the President : transmitted to the Congress February 1995 together with the annual report of the council of economic advisers (Washington : United States G.P.O., 1995)
Represents the annual report of the President's Council of Economic Advisers. Appendix B contains historical tables on aspects of income, production, prices, money stock, credit and finance, government finance, population, employment, wages, productivity, money and finance, corporate profit and finance, agriculture, international statistics and national wealth.
rpm 05/04/2017
Loans
Keywords: Labor market $1 (BUnited States.s; United States $1 (BEconomic policy $1 (BPeriodicals.s; United States $1 (BEconomic conditions $1 (BPeriodicals.s; Council of Economic Advisers (U.S.); United States